Optimized design and manufacturing of a motorcycle fairing spider. Issue 1 (31st December 2022) - Valerga, Ana P.; Huerta-Rodriguez, Marta; García-Ortiz, J. Hermenegildo
Abstract: In the racing world, weight is one of the key factors when developing a vehicle. Therefore, the aim is to reduce it as much as possible to achieve a good power/weight ratio that can be translated into increased speed, manoeuvrability, or reduced fuel consumption. For this reason, the trend is to redesign existing parts to obtain more optimised and lighter ones using new materials and complex structures that are often manufactured using 3D printing. In this manuscript, a spider or support for the fairing of a racing motorbike was designed, making use of topological optimisation techniques by means of Computer-Aided Design and using additive manufacturing. Specifically, PLA was used as an eco-friendly material to replace the conventional welded metal used in these areas of a motorbike. Theoretical and experimental tests were carried out to confirm the viability of the piece. With the analysis of the topological optimisation, it was possible to manufacture a sustainable, low weight and low cost part, which has never been manufactured before with a polymeric material.Keywords: Topologic, FEM, CAD, PLA, fused deposition modelling, Additive manufacturing